Pengaruh Multimedia Interaktif Terhadap Hasil Belajar Peserta Didik Kelas IV Sekolah Dasar - Prastya, Dicky (FKIP Universitas Lampung, 2017)
The influence of interactive multimedia to the learning achievement of fourth grade elementary students. This study aims to determine the effect of interactive multimedia Adobe flash to the learning achievement of fourth grade students of SD Negeri Glagah Yogyakarta in the integrative thematic learning subtema “Hebatnya Cita-Citaku” and evaluate the response of learners after applying Adobe Flash interactive multimedia. The study design used the nonequivalent control group. This research subjects in the experimental class is 30 Students of fourth grade and the control class is 29 Students of fourth grade in SD Negeri Glagah. The research instrument were interview, questionnaire responses of teachers, learners’ questionnaire responses, and test questions. Data were analyzed using independent sample t test with a significance level of 0.05. The results showed that Adobe Flash interactive multimedia provide significant impact on the learning outcomes of students. There are differences in the outcome between the experimental class and control class after using Adobe Flash interactive multimedia p < 0.05, then there is also a significant increase with p = 0.005. Keywords: interactive multimedia, learning outcomes, thematic integrative, scientific approachDOI: http://dx.doi.org/10.23960/jpp.v7.i1.201701